The Experience of Beauty of Chinese Poetry and Its Neural Substrates - Gao, Chunhai; Guo, Cheng (Frontiers in Psychology, 2018)
Chinese poetry has a long history and high aesthetic value. People who engage aesthetically with Chinese poetry would feel the sense of beauty naturally. However, there is little information regarding what happens in the brain when an individual appreciates Chinese poetry, and how the brain processes the subject’s appreciation of beauty. Herein, we used functional magnetic resonance imaging (fMRI) to investigate the neural substrates of experiencing beauty by appreciating Chinese poetry. The participants in our study were 28 college students and the stimuli consisted of 25 Chinese poetry and 25 prose selections. Based on an event-related paradigm, the ﬁndings of this study suggested that different areas scattered in both the left and right cerebral hemispheres are activated when an individual appreciates Chinese poetry. Compared to reading prose, appreciating Chinese poetry heightens the activation of the left inferior orbitofrontal cortex (OFC), the bilateral insula, the left fusiform, the left supplementary motor area (SMA), and the left precentral gyrus. In these areas, the left inferior OFC and the bilateral insula are considered closely related to experiencing beauty of Chinese poetry, which have been demonstrated that it is an important neural basis of aesthetic beauty when using other types of materials. The ﬁndings of this study shed new light on the complex but ordinary processes of experiencing beauty when appreciating Chinese poetry and show that some key processes underlying the feeling of aesthetic beauty are shared across different aesthetic domains.